Post-COVID-19 travel: factors influencing Malaysian tourists' travel intention to visit Japan / Karen Tsunokawa, Nabila Mohd Yunus and Muhammad Safuan Abdul Latip - Tsunokawa, Karen; Mohd Yunus, Nabila; Abdul Latip, Muhammad Safuan
Japan is one of the most popular tourist destinations. In 2019, more than 31 million inbound tourists visited Japan, and over 500,000 were from Malaysia. This number ranks ninth in the world in terms of the number of inbound tourists for Japan. Therefore, Malaysian tourists are an essential segment of the Japanese tourism industry. Additionally, the Japanese government has identified the tourism industry as a pillar of its growth strategy and set a goal of increasing the number of inbound tourists to 40 million by 2020 and 60 million by 2030. To achieve this goal, the factors influencing Malaysian tourists' intention to travel to Japan should be clarified and utilized for the effective and efficient development of the Japanese inbound tourism industry. However, no previous study has researched Malaysian tourists' intentions to visit Japan. Therefore, this research studies this area by examining Malaysian tourists living in Greater KL using the theory of planned behaviour and the push-pull factors theory. The examined factors include personal attitude, subjective norms, perceived behavioural control, and tourism resources. This research adopts the quantitative research method and collects a total of 359 valid responses, analysing the relationships between the factors and Malaysian tourists' traveling intention to visit Japan based on the collected data. As a result, the researcher finds that all the mentioned factors positively correlate with Malaysian tourists' intention to visit Japan.